Python Machine Learning Cookbook : Over 100 recipes to progress from smart data analytics to deep learning using real-world datasets, 2nd Edition /: Over 100 recipes to progress from smart data analytics to deep learning using real-world datasets, 2nd Edition. (2019) - Ciaburro, Giuseppe; Joshi, Prateek
No abstract available